МОНГОЛЫН ЗАГАСНЫ АЙМГИЙН ЗАРИМ ТӨРӨЛ ЗҮЙЛИЙГ МОЛЕКУЛ-ФИЛОГЕНЕТИКИЙН АРГААР СУДАЛСАН ДҮНГЭЭС - Дулмаа, Аюур (Proceedings of the Mongolian Academy of Sciences, 2016)
The Joint Mongolian-Russian Complex Biological Expedition is the biggest biological expedition in iterms of Water ecosystems of Mongolia. Over 40 years, large - scale integrated research has been analysis of natural and antropogenic processes and basic principles of rational exploitation. The aim is to fulfill complex hydrobiological, ichthyological and hydrological estimation of water resources state and propose measures for their protection Interrelation of global and local geo-climatic changes in territory of Mongolia in Cenozoic Era with evolution of endemic fishes of genera Oreoleuciscus is analysed. It is shown , that all basic stages of geo-climatic transformation directly defined occurrence, formation of species, morpho-ecological specialization and formation of geographic areas of species and their population organization.Evolutionary and population characteristics of the Altai osmans are given on the basis of genetically analysis of locuses mtDNA and the nuclear locuses coding isoenzymes. According to recent findings and investigations fauna of Lampreys and fishes of Mongolia consist of about 75 species of 14 families and 2 orders. 11 new species of fish, including one new invader bream (Abramis brama) were noted in the country waters last 15 years. According to new results two species of the Altai osmans (Oreoleuciscus angusticephalus, O.dsapchynensis) and one species of graylings (Thymallus arcticus) are excluded from the list of fish fauna of Mongolia. Recently Almai osmans were found not only in the waters of the Central-Asian closed basin, but also in rivers and small lakes of the Selenga River basin (Dgebuadze, Dulmaa, Munkhbayar 2003; Dulmaa A.,Munkhbayar Kh.Nakagawa M.,2004). Esseantial climate change and increasing of human impact transformed Mongolian fish population during last 40 years. As a result bias on ratio of ecological guilds, pathology number increasing, local diversity declining, and changes in species distribution, rate of growth and fecundity of many species of fish are observed. One of the main factors, influencing on fish populations, is gold mining in the rivers Arctic Ocean basin. In new conditions more attention demand both commercially important species as taimen, lenok, Baikal and Amur graylings, Amur carp, goldfish, Amur catfish, Amur and northern pikes, minnows, burbot, dace, and endangered and endemic species as Altai osman, Mongolian upper Enisey and Kosogol graylings, stone loaches and sculpin. Anthropogenic load on the water bodies of the Central-Asian closed basin is connected, first of all, with the constraction of hydraulic structures (dams in the basin of the Kobdo and Dzavkhan rivers), increase of pullution, and intensification of fishery. Evaluation of modern condition of water ecosystems and fish population parateters of this basin remains the main purpose of research for the years immediately ahead.